Ultrasonographic study on pastern soft tissue injuries in tent pegging horses - Zohier, A; Baraka , T; Abdelgalil, A; Aboelmaaty, A; Yehia, SG (Journal of the Hellenic Veterinary Medical Society, 2024)
Background: Pastern ultrasonography remains a useful and affordable choice, whether it is used in the field or when advanced imaging is not an option due to availability or cost considerations. Tent pegging is a high-speed sport practiced since the 4th century BC. There is a paucity of literature available about injuries associated with this type of sport. Aim of work: To study the incidence of soft tissue injuries at the pastern region in tent-pegging horses. Materials and methods: Ultrasonographic study was carried out on the palmar pastern region of 46 forelimbs (23 horses) to detect the different soft tissue injuries that occurred in association with this kind of sport. Results: Bilateral SDF chronic tendonitis was the highest percentage of the scanned affections, representing (52.2%). The most affected level in the SDFT was the right P1A (60.9%) and also showed a significant positive correlation with age. Conclusion: Long-term exposure to tent-pegging sports and poor rehabilitation programs lead to chronic tendonitis and adhesions, which subsequently lead to poor performance.